Establishing a Comprehensive Host-Parasite Stable Isotope Database to Unravel Trophic Relationships. - Sabadel, Amandine; Riekenberg, Philip; Ayala-Diaz, Monica; Belk, Mark C; Bennett, Jerusha; Bode, Antonio; Bury, Sarah J; Dabouineau, Laurent; Delgado, Josette; Finucci, Brittany; García-Seoane, Rita; Giari, Luisa; et al. (Springer Science and Business Media LLC, 2025)
Over the past decades, stable isotopes have been infrequently used to characterise host-parasite trophic relationships. This is because we have not yet identified consistent patterns in stable isotope values between parasites and their host tissues across species, which are crucial for understanding host-parasite dynamics. To address this, we initiated a worldwide collaboration to establish a unique database of stable isotope values of novel host-parasite pairs, effectively doubling the existing data in published literature. This database includes nitrogen, carbon, and sulphur stable isotope values. We present 3213 stable isotope data entries, representing 586 previously unpublished host-parasite pairs. Additionally, while existing literature was particularly limited in sulphur isotope values, we tripled information on this crucial element. By publishing unreported host-parasite pairs from previously unsampled areas of the world and using appropriate host tissues, our dataset stands unparalleled. We anticipate that end-users will utilise our database to uncover generalisable patterns, deepening our understanding of the complexities of parasite-host relationships and driving future research efforts in stable isotope parasitology.
Keywords: 4101 Climate Change Impacts and Adaptation; 41 Environmental Sciences; 2.2 Factors relating to the physical environment; 2.1 Biological and endogenous factors; Infection; Host-Parasite Interactions; Animals; Nitrogen Isotopes; Carbon Isotopes; Databases, Factual; Sulfur Isotopes; Parasites; Animals; Parasites; Carbon Isotopes; Nitrogen Isotopes; Sulfur Isotopes; Databases, Factual; Host-Parasite Interactions; Host-Parasite Interactions; Animals; Nitrogen Isotopes; Carbon Isotopes; Databases, Factual; Sulfur Isotopes; Parasites